Early low-dose hydrocortisone is associated with a reduced risk of bronchopulmonary dysplasia in infants born at less than 26 weeks' gestational age - Yao, Fang; Huang, Zhifeng; Chen, Xueyu; Yang, Chuanzhong; Li, Qiuping; Lin, Bingchun (Frontiers in Pediatrics, 2025)
ObjectiveTo determine whether administering low-dose hydrocortisone early in treatment reduces the risk of bronchopulmonary dysplasia (BPD) in infants born before 26 weeks of gestationStudy designThis retrospective case-control study compared the incidence of Grade II+ BPD between infants who received hydrocortisone treatment and those who did not. Propensity score matching was used to ensure comparability between the groups, with a 1:1 match ratio based on gestational age and birth weight.ResultsA total of 66 infants were included in the study. Those who received early low-dose hydrocortisone demonstrated a significantly lower risk of Grade II+ BPD incidence (p = 0.024). Additionally, early administration of low-dose hydrocortisone was associated with a shorter duration of non-invasive ventilation days (p = 0.038). Multiple logistic regression analysis confirmed that hydrocortisone treatment was independently associated with a reduced risk of Grade II + BPD incidence (OR: 0.287, 95% CI: 0.084–0.980).ConclusionsThese findings suggest that early administration of low-dose hydrocortisone is associated with a reduced risk of Grade II+ BPD in extremely preterm infants born before 26 weeks of gestation.